2013
DOI: 10.1021/ja402485j
|View full text |Cite
|
Sign up to set email alerts
|

Volume Change during Thermal [4 + 4] Cycloaddition of [2.2] (9,10)Anthracenophane

Abstract: We show that the reaction path connecting the tethered bi(anthracene-9,10-dimethylene) and its photodimer proceeds stepwise via a diradicaloid transition state where one σ-bond is made before a second. The newly found transition state (TS) has a smaller molecular volume than either the reactant or the product giving an atomistic explanation to the recently found pressure catalyzed barrier lowering and rate enhancement. The density functional methods used include long-range contributions as required in a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Unfortunately, the accuracy of the volume calculation (inside a contour of 0.001 electrons Bohr −3 ) turned out to be insufficient, providing implausible values of molar volumes and, as a consequence, activation and reaction volumes. Such calculation of reaction volumes has been previously employed to support the mechanism involving pressure acceleration of the [4+4] cycloaddition of [2.2] (9,10)anthracenophane . A considerably better approximation was achieved employing the volume of the cavity calculated using the Polarizable Continuum Model (PCM) of solvation.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the accuracy of the volume calculation (inside a contour of 0.001 electrons Bohr −3 ) turned out to be insufficient, providing implausible values of molar volumes and, as a consequence, activation and reaction volumes. Such calculation of reaction volumes has been previously employed to support the mechanism involving pressure acceleration of the [4+4] cycloaddition of [2.2] (9,10)anthracenophane . A considerably better approximation was achieved employing the volume of the cavity calculated using the Polarizable Continuum Model (PCM) of solvation.…”
Section: Resultsmentioning
confidence: 99%
“…The parameterization of a ChemDID model involves determining inter-molecular and intra-molecular potentials, the molecular mass and the inertial parameter for the dynamics of the molecule radii and as well as the coupling constants, ν meso and ν rad , that describe the coupling between the internal DoFs and the molecular centers of mass and radii. In this paper we parameterized a model reactive material with thermo-mechanical properties similar to anthracene, a molecular material believed to be capable of endothermic, volume reducing chemistry; DFT calculations by Slepetz et al [22] show that the low-volume endothermic state of anthracene has an energy between 10-20 kcal/mol over the high-volume ground state.…”
Section: B a Model Reactive Molecular Crystalmentioning
confidence: 99%
“…Such endothermic chemistry with volume reduction could provide the desired capability of shockwave energy dissipation. One possible system with such characteristics is the anthracene molecule; Jezowski et al [21] have found that the application of mechanical force reduces the rection rate involved in chemical bond formation, while Slepetz et al [22] have calculated a possible intermediate pathway occurring between reactants and products, which involves molecular volume reduction. With the potential energy fully determined in terms of the system variables, we can write the system Hamiltonian from which we will derive equations of motion:…”
Section: Coarse Grain Description Of Coupled Thermo-mechano-chemical mentioning
confidence: 99%